The impact of oxidative DNA damage and stress on telomere homeostasis - Barnes, Ryan P.; Fouquerel, Elise; Opresko, Patricia L. (Mechanisms of ageing and development, 2019)
•Loss of telomere maintenance contributes ageing-related diseases and carcinogenesis.•Numerous diseases associated with oxidative stress are also associated with shortened telomeres.•Studies in human tissues, mouse models and cell culture provide evidence that oxidative stress accelerates telomere shortening.•Telomeres are highly sensitive to oxidative DNA damage, which can induce telomere losses and dysfunction.•Base excision repair of oxidative damage is essential for telomere maintenance. Telomeres are dynamic nucleoprotein-DNA structures that cap and protect linear chromosome ends. Because telomeres shorten progressively with each replication, they impose a functional limit on the number of times a cell can divide. Critically short telomeres trigger cellular senescence in normal cells, or genomic instability in pre-malignant cells, which contribute to numerous degenerative and aging-related diseases including cancer. Therefore, a detailed understanding of the mechanisms of telomere loss and preservation is important for human health. Numerous studies have shown that oxidative stress is associated with accelerated telomere shortening and dysfunction. Oxidative stress caused by inflammation, intrinsic cell factors or environmental exposures, contributes to the pathogenesis of many degenerative diseases and cancer. Here we review the studies demonstrating associations between oxidative stress and accelerated telomere attrition in human tissue, mice and cell culture, and discuss possible mechanisms and cellular pathways that protect telomeres from oxidative damage.